The influence of service quality and price fairness on customer satisfaction toward Poslaju courier service - Halimi, Mimi Juliyana (2019)
Customer satisfaction refers to an important and critical issue in various industries and this research focus on the courier service industry. Improving customer satisfaction in the Poslaju courier service the service quality and price fairness are important predictors to determine customer satisfaction. Although the increasing number of customers consumes the Poslaju courier service, it is very important to understand customer needs and wants to create long term relationships. The aim of this study to determine the relationship between service quality and price fairness on customer satisfaction in the Poslaju courier service. This study applies the quantitative research method to measure the five dimensions of service quality including tangibles, reliability, responsiveness, assurance, and empathy. Then, price fairness also the factors on customer satisfaction. The sampling technique used is a clustered sampling technique. The questionnaire is distributed to the customer in the Poslaju courier service located at Kubang Pasu district. There are 334 respondents involved in this study. The data analysis is run by using SPSS version 25. The findings of multiple regression analysis reveal the result of the tangibles, reliability, responsiveness, assurance, and empathy as well as price fairness are significant toward customer satisfaction in the Poslaju courier service. Moreover, the assurance and price fairness variables are highly significant in customer satisfaction in this study.